2018
DOI: 10.20944/preprints201809.0042.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of OsCDPK1 on the Structure and Physicochemical Properties of Starch in Developing Rice Seeds

Abstract: Overexpression of a constitutively active truncated form of OsCDPK1 (OEtr) in rice produced smaller seeds, but a double-stranded RNA gene-silenced form of OsCDPK1 (Ri) yielded large seeds, suggesting that OsCDPK1 plays a functional role in rice seed development. In the study presented here, we propose a model in which OsCDPK1 plays key roles in negatively controlling the grain size, amylose content, and endosperm appearance, and also affects the physicochemical properties of the starch. The dehulled transgenic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Several PKs are involved in phytohormonal signaling transduction. OsCDPK1 plays key roles in negatively controlling the grain size, amylose content, and endosperm appearance [ 37 ]. Meanwhile, OsCDPK1 inhibits the feedback of GAs biosynthesis through down-regulating GA3ox2 and GA20ox1 [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several PKs are involved in phytohormonal signaling transduction. OsCDPK1 plays key roles in negatively controlling the grain size, amylose content, and endosperm appearance [ 37 ]. Meanwhile, OsCDPK1 inhibits the feedback of GAs biosynthesis through down-regulating GA3ox2 and GA20ox1 [ 91 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors NF-YB1 [ 33 , 34 ], RSR1 [ 35 ] and OsbZIP58 [ 36 ] were reported to be involved in chalkiness formation. OsCDPK1 was reported to affect the physicochemical properties of starch and plays key roles in negatively controlling the grain size, amylose content, and endosperm appearance [ 37 ]. Chalk5 [ 10 ], PDIL1-1 [ 38 ], BiP1 [ 39 , 40 ], OsVPS9A [ 41 ], OsRAB5A [ 42 ] and GPA3 [ 43 ] involved in protein metabolism were reported to mediate chalkiness formation.…”
Section: Introductionmentioning
confidence: 99%
“…In leaves, AGPases are known to be plastidial (Pérez et al, 2018). Furthermore, it has been shown that the grain size is altered when the starch structure changes (Matsushima et al, 2016; Wang, Zhang et al, 2018; Jiang et al, 2018). Hence, the expression of genes known to regulate seed size was examined in L_5 and L_6.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that CDPK and CRK genes were involved in the regulation of root, stem, leaf development, owering, pollen germination, pollen tube growth and seed development 4,21,22,28,[43][44][45][46][47] , as well as in the regulation of gibberellin, auxin, salicylic acid, abscisic acid and methyl jasmonate biosynthesis 27,[48][49][50][51][52][53] . In addition, they also played a role in biological and abiotic stress responses [54][55][56][57][58][59][60][61][62][63][64] .…”
Section: Discussionmentioning
confidence: 99%